Pelatihan Kesiapsiagaan Bencana Gempa Bumi pada Guru SMP di Kota Masohi Kabupaten Maluku Tengah - Nuliana, Wa; Imran, Andi Miftahul Khair; Dunggio, Abdul Rivai Saleh (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Maluku Province, including Central Maluku, is one of the areas where earthquakes occur most frequently and is at risk of causing problems in people's lives. To overcome the impacts, efforts need to be made to minimize losses due to earthquakes, namely by providing information about disaster preparedness through public facilities such as schools. This is supported by the participation of school stakeholders, one of which is teachers. This community service aims to increase the earthquake preparedness of SMPN teachers in Masohi City. This service activity was carried out through earthquake disaster preparedness training for 60 teachers from 3 SMPN schools in Masohi City, which included providing education, simulation mentoring, and evaluation. The results of this training were proven to be able to improve disaster preparedness for SMPN teachers in Masohi City as evidenced by the increase in the disaster knowledge score (KAP) from 69 to 82; emergency response plan (EP) from 75 to 85; disaster warning (WS) from 60 to 79; resource mobilization (RMC) from 57.4 to 76. Through this training, it is hoped that teachers, especially class teachers, can inform and train students and other teachers in disaster preparedness, especially earthquakes.